Assessing Medical Students’ Learning Preferences at Kabale University, Uganda - Muhaise, Hussein; Mbabazi, Phelix Busingye; Ssemaluulu, Paul; Kyomugishae, Patricia (East African Nature and Science Organization, 2023)
This article is based on an empirical study conducted to assess and establish the preferred learning styles of medical students in the Faculty of Medicine and Dentistry at Kabale University. The study was prompted by a paradigm shift in teaching-learning strategies from the conventional knowledge-based medical curriculum to competency-based medical education (CMBE). In line with the learners’ diversity and inclusion, CBME liberalises the learning environment by providing a variety of learning methods. Hence, the aim of this study was to ascertain the preferences of medical students’ learning styles in relation to the competency-based learning approaches. Procedurally, the study employed online survey methods, and the respondents included 160 medical (MBChB) students, all from the Faculty of Medicine and Dentistry. The data collected were captured on SPSS version 26 and subjected to t-test analysis. Besides, Visual, Aural, Read-Write, and Kinaesthetic (VARK) learning inventory was used to determine the students’ learning preferences, while a t-test was used to establish the relationships between the demographic profiles and the learning styles. Notably, the Aural learning style produced the highest mean score of 7.21 ± 3.61, followed by Kinaesthetic (6.43 ± 3.22), Read-Write (6.12 ± 2.23) and Visual (4.04 ± 2.42). Relatively, t-test results showed significant (p < 0.05) differences in learning styles between pre-clinical and clinical students. However, the t-test results for gender factors for all the learning dimensions were insignificant (p > 0.05). Pre-clinical students prefer visual and read-write learning styles, while clinical students prefer kinaesthetic and visual learning styles. Based on the findings, this study believes that identifying the learners’ preferred learning styles will help educators choose the most effective teaching methods.